Is Nanotechnology Helping in the Fight Against COVID-19? - Cardoso, Valéria Maria de Oliveira; Moreira, Bruna Juliana; Comparetti, Edson José; Sampaio, Isabella; Ferreira, Leonardo Miziara Barboza; Lins, Paula Maria Pincela; Zucolotto, Valtencir (Frontiers in Nanotechnology, 2020)
The novel coronavirus disease (COVID-19) pandemic represents an unprecedented public health concern. The disease, which presents an incredibly high spreading rate, was discovered in late December 2019, in Wuhan, Hubei province - China. The virus causing COVID-19, known as the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is responsible for the infection of more than 21.8 million individuals and more than 772 thousand deaths in 216 countries and still counting. Currently, there are no vaccines or antiviral treatments officially approved for the prevention or treatment of COVID-19, and since its appearance, several therapeutic approaches have been tested, including the use of repurposing drugs, such as broad-spectrum antivirals, nucleoside analogs, protease inhibitors, immunomodulators, plasma therapies, among others. However, these strategies have not shown great clinical benefits and are only administered to attenuate the symptoms. Although many therapeutic strategies are being tested against COVID-19, more efforts should be devoted to fighting the virus. Nanomaterials represent a powerful tool against COVID-19 since they can be designed to act directly toward the infection, increase the effectiveness of conventional antiviral drugs, or even to trigger the immune response of the patient. The advances in nanotechnology over the past decades allow us to develop new nanomaterials and step forward in the application of new technological tools. This review addresses the aspects related to the structural characteristics of the virus, mechanisms involved in the infection, and therapies currently used against COVID-19. Nanotechnology-based strategies to prevention, diagnosis, and treatment of COVID-19 will be discussed, including nanomaterials for face masks and surface sterilization, adjuvants, vaccine delivery nanosystems, and point-of-care tests, providing a perspective on how nanotechnology can be an allied in the fight against COVID-19.